MiRNA-mediated TUSC3 deficiency enhances UPR and ERAD to promote metastatic potential of NSCLC. Issue 1 (December 2018) - Jeon, Young-Jun; Kim, Taewan; Park, Dongju; Nuovo, Gerard; Rhee, Siyeon; Joshi, Pooja; Lee, Bum-Kyu; Jeong, Johan; Suh, Sung-suk; Grotzke, Jeff; Kim, Sung-Hak; Song, Jieun; et al.
Abstract Non-small cell lung carcinoma (NSCLC) is leading cause of cancer-related deaths in the world. The Tumor Suppressor Candidate 3 (TUSC3) at chromosome 8p22 known to be frequently deleted in cancer is often found to be deleted in advanced stage of solid tumors. However, the role of TUSC3 still remains controversial in lung cancer and context-dependent in several cancers. Here we propose that miR-224/-520c-dependent TUSC3 deficiency enhances the metastatic potential of NSCLC through the alteration of three unfolded protein response pathways and HRD1-dependent ERAD. ATF6α-dependent UPR is enhanced whereas the affinity of HRD1 to its substrates, PERK, IRE1α and p53 is weakened. Consequently, the alteration of UPRs and the suppressed p53-NM23H1/2 pathway by TUSC3 deficiency is ultimately responsible for enhancing metastatic potential of lung cancer. These findings provide mechanistic insight of unrecognized roles of TUSC3 in cancer progression and the oncogenic role of HRD1-dependent ERAD in cancer metastasis. TUSC3 resides on chromosome 8p which is frequently deleted in advanced stage tumors. Here, the authors show that TUSC3 loss mediated by miR-224/-520c promotes NSCLC metastasis where it enhances ATF-6α-dependent UPR and HRD-1 dependent ERAD, which in turn suppress p53-NM23H1/2 tumor suppressor pathway.